education and law - Kuleshov K. S., Soloveichenko E. G. (The Topical Issues of the Humanities and Social Sciences: from Theory to Practice, 2023)
The article examines the relationship between education and law. The author emphasizes that education is an important guarantee for the exercise of human rights, since educated people can better protect their rights and freedoms. The article also analyzes various aspects of the right to education, including access to education, the quality of education, the protection of the rights of students and teachers, as well as the freedom of scientific and creative work. The author calls for cooperation between educational and government institutions to ensure full access to education and protect the rights to education.
Keywords: образование; государство; правовое образование; право; Law Education State Protection Support Relationship Help Rules Law Student Institutions